2000
DOI: 10.1097/00007632-200005010-00006
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Vertebroplasty Using Osteoconductive Granular Material

Abstract: These results demonstrate the osteoconductivity of coral in granular form for vertebral filling. Interestingly, interconnectivity between adjacent bone trabeculae and newly formed bone was restored; however, its mechanical significance remains to be determined. Further investigations are needed to evaluate the efficacy of coral in osteopenic animals and in relieving pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(34 citation statements)
references
References 10 publications
0
34
0
Order By: Relevance
“…Absorption of calcium carbonate can be visualized by radiographs and ex vivo by histomorphometric [22]. In contrast, CPC absorption has been described only by histomorphometric measurements but not by radiological examinations because of the slower absorption rate compared with CaCO 3 [9,10,22].…”
Section: Discussionmentioning
confidence: 99%
“…Absorption of calcium carbonate can be visualized by radiographs and ex vivo by histomorphometric [22]. In contrast, CPC absorption has been described only by histomorphometric measurements but not by radiological examinations because of the slower absorption rate compared with CaCO 3 [9,10,22].…”
Section: Discussionmentioning
confidence: 99%
“…The accelerated cell growth might have resulted from the interaction of the hPDCs with components of the fibrin sealant or from differences in substrate stiffness. The major components of fibrin, fibrinogen and thrombin, have both been found to stimulate proliferation of fibroblasts and osteoblasts when added to the culture medium or when bound to the cell culture substrate (Dawes et al, 1993;Gray et al, 1993;Gorodetsky et al, 1998;Frost et al, 1999). Besides fibrinogen and thrombin, fibrin sealants can also contain active growth factors including TGF-1 and bFGF (Cox et al, 2004).…”
Section: J Demol Et Al Fibrin For Osteogenic Differentiation Of Hpdcs?mentioning
confidence: 99%
“…However, not all studies obtained the same result. Some studies attributed excellent osteogenic and osteoinductive properties to fibrin (Kania et al, 1998;Tholpady et al, 1999;Isogai et al, 2000;Perka et al, 2000;Abiraman et al, 2002;Kalia et al, 2009), while others reported nonsignificant positive and negative results (Jarzem et al, 1996;Brittberg et al, 1997;Carmagnola et al, 2000;Cunin et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adjunction of a binding agent such as fibrin glue may stabilize the granules in the implantation site and produce a composite that can be moulded into the defect without empty spaces. 8,9 Many processing routes have been used for the fabrication of porous hydroxyapatite granules, such as hydrothermal conversion of natural corals 10 and crushing of sintered blocks, granulation by vibration and rolling, 11 dripping procedure, 12 casting in plaster mould, 13 emulsion methods 14,15 and the spraydrying process. 16 However, these processes do not yield granules with optimal properties for medical applications.…”
Section: Introductionmentioning
confidence: 99%